FENOMENA LGBT DALAM PERSPEKTIF HUKUM ISLAM (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2016)
Al-qur’an is given to human as life guidance which contains a lot of regulations.  Marrieage is one of the regulations. A marriage in Islam is between different sex types, that is man and woman. Marriage is not only about to have biological sex desire but also as a holy relationship to create harmonious life by building sakinah family and growing good descants. A marriage done by hoomosexual and lesbian community will not give any function and even can endanger human generation.LGBT stands for lesbian, gay, bisexual and transgender. Lesbian means a woman who do sex with other woman. Gay is homosexual people. Bisexual defined as people with two sex interests. This kind of person do sex both with woman and man. The increasing of LGBT phenoemenon in all aspects of life, which is why Islam gives explanation and clear regulation for this problem.